Consumer Purchasing Behaviour towards Eco-Friendly Products in Salem - N. Shanthi,; Dr. D. Thiruniraiselvi, (IJRDO - Journal of Business Management, 2025)
The environment is being destroyed through industrialisation and unsustainable consumer trends which have increased the emphasis on eco-friendly products and green marketing in the world. This research paper examines the reason why people in Salem City will purchase eco-friendly products and in particular how the environmental concern and features of a product can affect the decision made by consumers.  This was an empirical approach to research which collected primary data in form of interviews. A total of 186 participants who were selected through snowball sampling were surveyed. The type of SPSS-20 exploratory factor analysis combined with KMO=0.762 and chi-square Bartlett of 4292.355(p=0.001) showed that the data used were appropriate in the analysis. Factor analysis identified that there were four principal factors in consumer purchase: (i) product offers about environmental protection, (ii) special promotions of any product that emphasize the eco-features, (iii) reusability and curiosity, and (iv) less exploiting nature. These dimensions indicate that price, environmental knowledge and social indicators all intertwine to influence preferences. When the products are affordable, readily available, and well advertised, consumers are more likely to opt on products that have been eco friendly. Buyers are also motivated more by the concern of environmental protection and their belief in the quality of the green products.